Calculating facility siting study leak sizes‐one size does not fit all. Issue 2 (10th August 2015) - Fitzgerald, Gary Allen
Abstract : Consequence‐based Facility Siting Studies (FSSs) typically require the user assume a credible leak size to use in the evaluation of potential releases, which is often up to a 2 inch diameter leak. Many facilities tend to be less complex in comparison to large refineries or petrochemical plants, leading operators at the less complex facilities to ask why they should assume the same leak sizes as more complex facilities. Other facilities have unique processes with safety systems and factors they would like to quantify in a consequence‐based FSS. A unique approach developed by ABS Consulting and first presented in 2011 is called the Maximum Design Leak (MDL) approach (Fitzgerald et al., 2011 Mary Kay O'Connor Process Safety Center International Symposium, October 25, 2011). This approach calculates frequency‐based leak sizes and then applies the leak size that exceeds a frequency criterion (events/year) in a consequence‐based FSS instead of assuming a given leak size as credible. This avoids having to establish risk criteria in terms of fatalities/year and having to model a large number of scenarios yet takes advantage of many features in a Quantitative Risk Assessment (QRA). This article presents three case studies as examples of how the MDL has been applied and illustrates the advantages of calculating leak sizes specific to scenarios being evaluated for low complexity and low risk facilities. © 2015 American Institute of Chemical Engineers Process Saf Prog 35: 176–178, 2016